Study on passengers satisfaction on facilities management services in Kuala Lumpur Central Railway Station / Amirah Abdullah and Nor Nazihah Chuweni - Abdullah, Amirah; Chuweni, Nor Nazihah (2019)
Facilities Management services is one of the important aspect in order to determine and ensure the passenger satisfaction to any product or services provides including transportation system. Nowadays, transportation system become a quite vital system that contribute to the growing of economic development especially the contribution of railway station. This paper examined the basic facilities at the railway station and determine the level of passengers'satisfaction with facilities management services in railway station. This study employed both qualitative and quantitative method to achieve the objectives. İnterview was conducted with the facilities manager to identify the basic facilities at the railway station. On the other hand, questionnaires have been distributed to the passenger in Kuala Lumpur Sentral Railway Station. The results from questionnaires revealed that the top highest of level passenger satisfaction is information system factor in the station. While, lowest mean score among the level of passenger satisfaction is emergency factor compared to other factors namely service, safety, information system, ventilation, and comfort. Therefore, the facilities management department in Kuala Lumpur Sentral Railway Station need to take proactive actions to overcome this problem to ensure the high level on passenger satisfaction in term of facilities management in the station.